PENGEMBANGAN GAME EDUKASI INTERAKTIF EKSPLORASI SEJARAH ISLAM DI JAWA BARAT (STUDI KASUS MADRASAH ALIYAH ASSALAM MAJA) - Sondara, Muhammad Raka; Prasetyo, Tri Ferga (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
Over time, the use of technology has become important in various aspects of daily life. One example is the field of education, the development and utilization of technology in learning can increase student interest because it offers a more interactive and dynamic learning experience. This study aims to develop an interactive educational game exploring Islamic history in West Java, with a case study at the Assalam Maja Madrasah Aliyah School. This game was developed to help students understand Islamic history material, especially Islamic history in West Java. The development methodology used is the GDLC Model, which involves the stages of initialization/concept creation, preproduction, creation, testing, beta, and launch. This educational game allows students to learn Islamic history in West Java through interactive quizzes and visually presented materials. The test results comparing conventional methods with this game, which are calculated using the N-Gain Score, show that this game is quite effective in improving students' understanding of Islamic history in West Java with a value range of 0.6. It is hoped that the development of this interactive educational game of Islamic history in West Java can be an alternative effective learning media.